Historical Study: Conceptual Study Of The Origin Of The Muslim Community In Pegayaman Village, Sukasada District, Buleleng Regency, Bali - Raisyabilla, Rangga Octava; Alhail, Hadi; Musthafa, Akram; Tricahya, Krishna; Utama, I Gusti Agung Gede Aditya; Sasea, Sanita Carolina; Afifi, Wayan M Aziz; Putri, Adesti Anggita (Jurnal Pendidikan Sejarah, 2025)
Historical Study of Pegayaman Village, Buleleng, Bali This journal examines the origin of Pegayaman Village, Buleleng, Bali, through a conceptual study of its history. This research is motivated by the lack of conceptual understanding of village history for the younger generation and the need for regeneration of local historians. The exploratory qualitative research method was applied with a focus on Banjar Dinas Barat Jalan, Pegayaman Village. Primary data was obtained through interviews and direct observations, while secondary data was obtained through observation and interviews with the main source. The results of the study show that the origin of Pegayaman Village is divided into 5 phases: 1. Threat and Conflict Phase: Pegayaman Village became a fortress for the defense of the Buleleng Kingdom from the attacks of the southern kingdom. 2. Recruitment Phase of 100 Muslim Laskar Blambangan: The Kingdom of Buleleng received the assistance of 100 Muslim Laskar from Blambangan to guard its territory. 3. Appreciation Phase with the Handover of Gatep Forest: Muslim soldiers were given gatep forest land as a form of appreciation for their services. 4. Phase of Naming the Area into Pegayaman Village: The name "Pegayaman" comes from the word "gayam", referring to the gatep fruit and keris gayaman, a symbol of strength and resilience. 5. Strategic Phase of Pegayaman as a Fortress of Defense, Identity Formulation and Value Conservation: Pegayaman Village has developed into a village with 6 superior identities, such as a historical village, an old village, a warrior village, and an acculturative village. This journal concludes that Pegayaman Village has a rich and unique history, formed through the acculturation of Islamic-Hindu culture and religion. This village is a real example of tolerance between religious communities in Bali, with a rich cultural heritage and tradition as a result of the acculturation.